ON STRONG ALMOST A-SUMMABILITY WITH RESPECT TO A MODULUS AND STATISTICAL CONVERGENCE - SAVAS, E (Indian Nat Sci Acad, 1992)
The definition of strong A-summability with respect to a modulus is extended to a definition of strong almost A-summability with respect to a modulus when A is non-negative almost regular matrix summability method. It is shown that if a sequence is strongly almost A-summable with respect to an arbitrary modulus then it is almost A-statistically convergent and that almost A-statistically convergence and strong almost A-summability with respect to a modulus are equivalent on the bounded sequences.